Application of Growth Hormone in in vitro Fertilization - Xu, Yue-Ming; Hao, Gui-Min; Gao, Bu-Lang (Frontiers in Endocrinology, 2019)
Growth hormone (GH) is a peptide hormone secreted mainly by the anterior part of the pituitary gland and plays a critical role in cell growth, development, and metabolism throughout the body. GH can not only directly influence human oocytes and cumulus cells but also indirectly improve oocyte quality through activating synthesis of insulin-like growth factor-I or promoting follicle-stimulating hormone-induced ovarian steroidogenesis. Since GH can regulate female and male infertility, it has been applied in the management of infertility for many years, especially in patients with poor ovarian response or poor prognosis. During ovarian stimulation, GH administration might improve the success rate of in vitro fertilization (IVF) probably through the beneficial effects of GH on oocyte quality as indicated by a higher number of mature oocytes and embryos arriving at the transfer stage and a higher fertility rate in GH-treated patients. However, there is still great controversy in the application of GH in IVF. While some researchers showed that pregnancy, implantation and live birth rates could be increased by ovarian pretreatment with GH, others did not support GH as an effective adjuvant for infertility treatment because the live birth rate was not increased. This study reviewed and summarized recent advancements and benefits in clinical application of GH, trying to reach a just unbiased conclusion regarding the effect of GH therapy in IVF.